Accumulation condition analysis of the Permian shale gas in the Turpan‐Hami Basin, Northwest China. (20th March 2019) - Dang, Ben; Zhao, Hong; Chen, Jun; Zheng, Yong; Xu, Ming; Lin, Lujun; Liu, Ming; Liang, Bin; Cao, Liu; Qin, Haoliang; Zhang, Yue
Abstract : The north‐western region of China is one of the five major shale gas evaluation zones in China. The Turpan‐Hami Basin is one of the important petroliferous basins in the north‐west of China. However, shale gas study in this basin has just started. In this study, based on the investigation of the field outcrop section on the periphery and core observation of this basin, combined with extensive experimental analysis, the Permian dark shale has been studied comprehensively including the development distribution characteristics of the shale, brittle mineral composition, organic geochemistry, physical property, and the gas content. The results show that the dark shale are mainly developed in the middle Permian Taerlang Formation and mainly distributed in the Taibei, Toksun, and Tainan sags in the Turpan Depression and the Sanbu and Huoshizhen sags in the Hami Depression. The northern margin and the western margin of the basin and the south of the Liaodun Uplift are exposed to different degrees. Thickness of the dark shale is between 100 and 500 m with the buried depth of 160–3, 600 m. The dark shale is mainly deposited in shallow lacustrine and semideep lacustrine facies. The shale is composed mainly of clay minerals (average 44.6%), brittle mineral quartz (average 38.9%), feldspar (average 9.7%), and calcite (average 4.0%). Brittle mineral contents are high, accounting for 52.6%. The dark shale with an organic carbon content more than 2% accounts for 80% in the tested samples. The types of organic matter are commonly Type II2, followed by Type III. The degree of organic thermal evolution is moderate. The majority areas are in the low‐mature and mature stage, while some areas achieve high maturity stage. The gas content ranges from 0.11 to 6.29 m 3 /t. Comprehensive analysis shows that the Permian Taerlang Formation dark shale in Turpan‐Hami Basin has the shale gas accumulation conditions. The favourable areas are mainly located in the Taibei Sag in the Turpan Depression, the south of the Liaodun Uplift, followed by the Toksun and Tainan sags in the Turpan and the Hami Depressions.